2014
DOI: 10.1590/1983-1447.2014.04.50716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fall risk factors in adults within the first 48 hours of hospitalization

Abstract: Objective: To analyze fall risk factors in the first 48 hours of hospitalization and to associate them with the occurrence of falls. Method: Cohort study conducted at a hospital in Porto Alegre/RS, Brazil. A sample of 556 patients from an adult in-patient study population were evaluated within the first 48 hours of hospitalization for factors associated with falls, based on the Morse Fall Scale (MFS) and muscle strength, among others. Results: Evidence showed that the classification of high-risk according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
2
14
0
12
Order By: Relevance
“…Falls from bed were the second most common: 22.9% and 17.9% of the test and validation samples, respectively. These findings are similar to those of other studies (Pasa et al., ; Remor et al., ). Patients spend most of their time in the bedroom while hospitalized, rather than the bathroom or corridors, which explains the higher prevalence of falls there (Prates et al., ; Victor et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Falls from bed were the second most common: 22.9% and 17.9% of the test and validation samples, respectively. These findings are similar to those of other studies (Pasa et al., ; Remor et al., ). Patients spend most of their time in the bedroom while hospitalized, rather than the bathroom or corridors, which explains the higher prevalence of falls there (Prates et al., ; Victor et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the classification of falls risk favors the planning of interventions with the purpose of preventing this adverse event (22) . Another study which used the Morse Scale to analyze risk factors for falls in the first 48 hours of hospitalization and associate them with the occurrence of falls, also found a statistical association between visual impairment and occurrence of falls, since 88.6% of those who (previously) fell had this impairment (23) . It is important to emphasize that this risk factor is little emphasized in existing studies related to the risk of falls.…”
Section: Discussionmentioning
confidence: 95%
“…The use of the Morse Scale was effective in other studies because its use showed high sensitivity in classification (25) since the great majority of patients who fell had a high risk for falls (23) . One study analyzed the Morse Scale in hospitalized Portuguese adult patients in association with their characteristics, diagnosis and length of stay, evidencing that several risk factors for falls are not evaluated by it; a result that is in agreement with the results of this study (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, some strategies can be cited that can be included in the care plan: use specific instruments to predict the risk of falls, one of which is the MFS: train the team on the appropriate way to assess the patient and implement the strategies; advise patients/companions on the risk factors that can entail falls; and identify high-risk patients, using a signal at the headrest or a specific wristband, among other strategies 7 - 8 , 22 .…”
Section: Discussionmentioning
confidence: 99%